Uji Kadar Zat Besi (Fe) Sediaan Obat Tablet Tambah Darah (Ferro Fumarat) dengan Metode Kompleksometri - Ratih Nurwanti; Hasty Hamzah; Nurdiyanti (Politeknik Baubau, 2023)
Iron is a very important element to form hemoglobin (Hb). Blood supplement tablets which are often consumed in the process of g iron are ferro fumarate. The aims is determine the levels of iron (Fe) contained in blood supplement drugs (ferro fumarate). This type of research was a laboratory experiment using the complexometric method and a complex forming substance, namely disodium ethylene diamine tetra acetate (Na2EDTA). A sample of blood supplement tablets (ferro fumarate) which was prepared in 10 tablets was made into powder and then 150 mg was taken and titrated with Na2EDTA as the titrant and using the Erichrome Black T (EBT) indicator resulting in a purple titration end point turning blue. The results showed that the level of iron (Fe) in the blood supplement sample (ferro fumarate) was 200%.